ANALYSIS OF FACTORS THAT INFLUENCE CONSUMER DECISIONS IN USING THE GOJEK APPLICATION WITH GO-FOOD FEATURES IN BANJARMASIN CITY - Minarti Limantara; Laila Refiana Said (International Journal of Economic Integration and Regional Competitiveness, 2024)
This study aims to analyze the factors of price, promotion, culture, individual and social influence simultaneously (together) on consumer decisions in using the Go-Food Feature Go-Jek application in the city of Banjarmasin. The research method is an explanatory research. The sample size was taken using the Slovin formula and the results were 100 respondents (rounded up to represent the total population). The sampling technique used the purposive sampling method. The purposive sampling method is a sampling technique with certain considerations. The analysis technique uses multiple linear regression analysis using SPSS 21.0 for windows. Based on the results of the research and analysis obtained, it can be concluded that the price, promotion, culture, individual, and social factors simultaneously (together) have a significant effect on consumer decisions in the use of the go-food feature go- food application in the city of Banjarmasin. The price factor partially has no significant effect on consumer decisions in using the go-food feature go-food application in the city of Banjarmasin. Promotion factor partially has no effect and significance on consumer decisions in using the go-food feature go-food application in the city of Banjarmasin. Cultural factors partially have no effect and significance on consumer decisions in using the go-food feature go-food application in the city of Banjarmasin. Individual factors partially have a significant effect on consumer decisions in using the go-food application feature of go-food in the city of Banjarmasin. Partial social factors have no significant effect on consumer decisions in the use of the go-food application feature go-food in the city of Banjarmasin.